O mal como condição humana: a negação da morte e seus desdobramentos em Ernest Becker - Guzman, Soemis Martinez (2011)
Ernest Becker targeted to understand the human condition by stating that the fear of death is the terror installation at the psychological base of man, from this realization he produced a work constituted by a synthesis of thoughts based on Kierkegaardian philosophy and psychoanalysis derived from Freud and his collaborators, with emphasis on Otto Rank, and a Darwinian evolution approach thus characterizing his interdisciplinarity. He believed it to be necessary the perception of being and society the true knowledge base in the description of the motivation that takes us to our condition. For this, he suggested that the fear of death and its denial are universal fundamental facts for every human activity and that the heroism product of this fear is the main human problem. As a starting point he uses the problem of heroism in contemporaneous society and shows the denial of finitude in modern culture. So, in its quest for transcendence, humanity creates symbols which further distances, from its perception of reality as species